2001
DOI: 10.1093/emboj/20.15.4299
|View full text |Cite
|
Sign up to set email alerts
|

G-overhang dynamics at Tetrahymena telomeres

Abstract: To learn more about the structure of the DNA terminus at Tetrahymena thermophila telomeres, we have devised a ligation-mediated primer extension protocol to accurately measure the length of the G-strand overhang. We show that overhang length and the identity of the 3¢-terminal nucleotide are tightly regulated. The majority of overhangs terminate in the sequence 5¢-TTGGGGT and >80% are either 14±15 or 20±21 nucleotides in length. No signi®cant changes in overhang length were detected as cells traversed the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 45 publications
6
64
0
2
Order By: Relevance
“…Tetrahymena cells were grown in 1.5ϫ PPYS at 30°C as previously described (20). CdCl 2 was added to 2 g/ml to maintain the expression of the rescuing POT1a allele.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrahymena cells were grown in 1.5ϫ PPYS at 30°C as previously described (20). CdCl 2 was added to 2 g/ml to maintain the expression of the rescuing POT1a allele.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting ϳ40,000 macronuclear telomeres are composed of 250-to 350-bp G 4 T 2 /C 4 A 2 repeats. These telomeres have a very precise terminal DNA structure, as the C strands end with the sequence 5Ј C 3 A 2 -or 5Ј C 2 A 2 -, while most G strands extend another 14 or 15 nucleotides (nt) or 20 or 21 nt and terminate with the sequence 5Ј-T 2 G 4 T (20). Studies with telomerase-deficient cells have revealed that this precise G-overhang structure is generated by a series of specific G-and C-strand processing reactions (21).…”
mentioning
confidence: 99%
“…7). Tetrahymena telomeres are capped by Pot1a in complex with Tpt1, Pat1, and Pat2 (25,26), bound to an overhang of 14 to 15 or 20 to 21 nucleotides with a TGGGGT-3=OH end permutation (45,46). This length of overhang is insufficient for binding both Pot1a and Teb1 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Diverses expériences suggèrent que des extensions G-riches sont présentes sur tous les télomères, aux deux extrémités des chromosomes macronucléaires [9]. Ces extensions sont détectées durant tout le cycle cellulaire [10]. La taille exacte des extensions, ainsi que leur séquence, sont contrôlées très strictement chez les ciliés.…”
Section: Débuts Chez Les Ciliésunclassified
“…La taille exacte des extensions, ainsi que leur séquence, sont contrôlées très strictement chez les ciliés. La majorité des extensions se termine par la séquence 5'-TTGGGGT-3' et plus de 80 % de ces extensions ont 14-15 ou 20-21 nucléotides [10]. Cependant, leur taille peut varier lorsque les cellules sont soumises à certaines restrictions nutritionnelles ou lorsqu'elles sortent du cycle cellulaire.…”
Section: Débuts Chez Les Ciliésunclassified